Multi-dimensional genomic analysis of myoepithelial carcinoma identifies prevalent oncogenic gene fusions. Issue 1 (December 2017) - Dalin, Martin; Katabi, Nora; Persson, Marta; Lee, Ken-Wing; Makarov, Vladimir; Desrichard, Alexis; Walsh, Logan; West, Lyndsay; Nadeem, Zaineb; Ramaswami, Deepa; Havel, Jonathan; Kuo, Fengshen; et al.
Abstract Myoepithelial carcinoma (MECA) is an aggressive salivary gland cancer with largely unknown genetic features. Here we comprehensively analyze molecular alterations in 40 MECAs using integrated genomic analyses. We identify a low mutational load, and high prevalence (70%) of oncogenic gene fusions. Most fusions involve thePLAG1 oncogene, which is associated withPLAG1 overexpression. We findFGFR1-PLAG1 in seven (18%) cases, and the novelTGFBR3-PLAG1 fusion in six (15%) cases.TGFBR3-PLAG1 promotes a tumorigenic phenotype in vitro, and is absent in 723 other salivary gland tumors. Other novelPLAG1 fusions includeND4-PLAG1 ; a fusion between mitochondrial and nuclear DNA. We also identify higher number of copy number alterations as a risk factor for recurrence, independent of tumor stage at diagnosis. Our findings indicate that MECA is a fusion-driven disease, nominateTGFBR3-PLAG1 as a hallmark of MECA, and provide a framework for future diagnostic and therapeutic research in this lethal cancer. Myoepithelial carcinoma (MECA) is a rare aggressive salivary gland cancer. Here, the authors analyze the genomic landscape of MECA and identify a high prevalence of oncogenic gene fusions, primarily PLAG1 fusions, highlighting TGFBR3-PLAG1 as a potential hallmark of MECA.